2010
DOI: 10.1242/dev.052944
|View full text |Cite
|
Sign up to set email alerts
|

Arginine methylation of SmB is required for Drosophila germ cell development

Abstract: SUMMARYSm proteins constitute the common core of spliceosomal small nuclear ribonucleoproteins. Although Sm proteins are known to be methylated at specific arginine residues within the C-terminal arginine-glycine dipeptide (RG) repeats, the biological relevance of these modifications remains unknown. In this study, a tissue-specific function of arginine methylation of the SmB protein was identified in Drosophila. Analysis of the distribution of SmB during oogenesis revealed that this protein accumulates at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 52 publications
(70 reference statements)
0
20
0
Order By: Relevance
“…Functional analyses have shown that the PRMT5/PIWI/TUDOR network plays a role in the piRNA processing pathway, retrotransposon silencing and, consequently, genomic stability (Nishida et al, 2009;Reuter et al, 2009;Shoji et al, 2009;reviewed by Siomi et al, 2011). By contrast, the PRMT5/Sm/TUDOR network present in fly oocytes is involved in localization of oskar mRNA and specification of germ cell fate (Anne et al, 2007;Anne, 2010;Boswell and Mahowald, 1985;Gonsalvez et al, 2006;Gonsalvez et al, 2010). Our biochemical and sequence analyses suggest that both SMEDWI-3 and Sm protein family members are methylated in planarians.…”
Section: Planarian Chromatoid Body Function and The Role Of Methylationmentioning
confidence: 66%
See 1 more Smart Citation
“…Functional analyses have shown that the PRMT5/PIWI/TUDOR network plays a role in the piRNA processing pathway, retrotransposon silencing and, consequently, genomic stability (Nishida et al, 2009;Reuter et al, 2009;Shoji et al, 2009;reviewed by Siomi et al, 2011). By contrast, the PRMT5/Sm/TUDOR network present in fly oocytes is involved in localization of oskar mRNA and specification of germ cell fate (Anne et al, 2007;Anne, 2010;Boswell and Mahowald, 1985;Gonsalvez et al, 2006;Gonsalvez et al, 2010). Our biochemical and sequence analyses suggest that both SMEDWI-3 and Sm protein family members are methylated in planarians.…”
Section: Planarian Chromatoid Body Function and The Role Of Methylationmentioning
confidence: 66%
“…Y12 specifically recognizes sDMA (Brahms et al, 2000), suggesting that neoblasts express machinery necessary for this modification. Recent reports have shown that interactions between proteins containing sDMA and TDRDs are important for RNP aggregation in mouse and fly germlines (Anne, 2010;Gonsalvez et al, 2010;Kirino et al, 2010b;Vagin et al, 2009b). Given that neoblasts are enriched with expression of tudor homologs Yoshida-Kashikawa et al, 2007) and that one homolog is a neoblast CB component (Solana et al, 2009), we analyzed sDMAcontaining proteins in neoblasts.…”
Section: Planarian Neoblasts Are Enriched With Sdmacontaining Proteinmentioning
confidence: 99%
“…In higher eukaryotes, PRMTs can regulate cell development and differentiation. For example, in Drosophila , arginine methylation by their PRMTs (DARTS) has been linked to establishment of germ cells and wing development (Anne ; Xu et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…In Caenorhabditis elegans , Sm proteins, but not other splicing factors, localize to germline P granules and are required for their integrity [19,20]. In Drosophila melanogaster , SmB and SmD3 are enriched at the posterior pole of developing oocytes [21,22], and a hypomorphic mutation in SmD3 causes mislocalization of oskar mRNPs and pronounced defects in germ cell specification that are independent from splicing [21]. Moreover, loss of the Sm protein methyltransferase PRMT5 results in failure to specify the germline [21,23,24].…”
Section: Introductionmentioning
confidence: 99%